Measuring poverty in the Philippines application of the demographic and health survey welath indices in the 2013 young adult fertility and sexuality survey - Tabaco, Rea Jean P.
The accurate indentification of the poor population is essential in the success of poverty reduction programs. In view of this, the study employed the Demographic and Health Survey (DHS) wealth index to measure poverty in the Philippines. Using the 2013 Young Adult Fertility and Sexualtiy (YAFS) data, the study applied two methods of generating wealth indices - the Classical Wealth Index and the Urban-Rural Wealth Index. For each method, two sets of variables were used: the first set transformed all variables into indicator variables while the second set transformed all variables into indicator variables except for ownership of appliances and vehicles which used the number of owned assets. The poor population were identified as those with the lowest 25.2% wealth scores following the 2012 official poverty incidence. The study produced four regional poverty estimates. These estimates have no substantial differences among each other and all were found to have strong relationship with the official poverty statistics in terms of distribution (Index of Dissimilarity value = 0.8) and ranking (Spearman's rho values ranged from 0.87 to 0.89). The application of the poverty estimates to teenage pregnancy and internet use indicators reflects the relationship with poverty found in previous studies.